2015
DOI: 10.1134/s1063780x15040054
|View full text |Cite
|
Sign up to set email alerts
|

X-pinch. Part I

Abstract: Results of experimental studies of the Х-pinch since its invention and implementation in 1982 at the Lebedev Physical Institute are presented. The concept of the Х-pinch arose in the course of innovative experiments on studying the generation of hot dense plasma in nanosecond Z-pinches. The main idea was to localize the region occupied by the plasma and stabilize the moment of its formation. This was achieved by using a load in the form of crossed wires. The resulting plasma object turned out to be so interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(40 citation statements)
references
References 165 publications
2
38
0
Order By: Relevance
“…1a), made 20 ns later, a cavity is seen at the neck place that was formed obviously due to the explosion of the hot spot. Similar pictures were obtained [20,21] for X pinches also consisting of two molybdenum wires of diameter 17 µm the current through which at the time of the explosion was 150-170 kA. These images, taken in soft x rays, clearly demonstrate the explosion of the hot spot.…”
supporting
confidence: 61%
See 3 more Smart Citations
“…1a), made 20 ns later, a cavity is seen at the neck place that was formed obviously due to the explosion of the hot spot. Similar pictures were obtained [20,21] for X pinches also consisting of two molybdenum wires of diameter 17 µm the current through which at the time of the explosion was 150-170 kA. These images, taken in soft x rays, clearly demonstrate the explosion of the hot spot.…”
supporting
confidence: 61%
“…At the end, the hot spot explodes and at this time, hard x rays and high-energy ions are generated. The ions appear with a slight delay after the main pulse of soft x rays [21]. This scenario is illustrated by Figs.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…The plausibility of this chain of events became clear in an extensive set of laboratory studies using Z-pinches, plasma foci and X-pinches (Pikuz et al, 2015a(Pikuz et al, , 2015b. Although not motivated by astrophysical connections, these studies revealed effects that could be of relevance to astrophysics: the formation of energetic, non-thermal ion populations, and generation of particle beams.…”
Section: B Generation Of Energetic Particlesmentioning
confidence: 99%